(untitled) (Agora for Physical Education and Sport, 2021)
Venezuelan Physical Education has historically gone through various tendencies: militaristic, athletic, and hygienic-medical, among others. These notions of Physical Education are classified as conservative of the status quo, and they are accused of a system that maintains logics of authoritarianism, inequality, segregation and discrimination, in reproduction of prevailing social logics since 1958 after the overthrow of the Perezjimenista dictatorship. However, there is a historical break, and this work has the purpose of presenting this experience in the context of a Physical Education that emerges from other sensibilities that echo the denunciations of the widening of socio-political gaps and their consequences. It is concluded that the current Physical Education points much more to the practice of a critical Physical Education, generating changes in its assumption and revitalizing spaces in the school until now co-opted.